Myocardial injury in patients with SARS‐CoV‐2 pneumonia: Pivotal role of inflammation in COVID‐19. (11th November 2021) - Melillo, Francesco; Napolano, Antonio; Loffi, Marco; Regazzoni, Valentina; Boccellino, Antonio; Danzi, Gian Battista; Cappelletti, Alberto Maria; Rovere‐Querini, Patrizia; Landoni, Giovanni; Ingallina, Giacomo; Stella, Stefano; Ancona, Francesco; et al.
Abstract: Aims: Infection by SARS‐CoV‐2 may result in a systemic disease and a proportion of patients ranging 15%–44% experienced cardiac injury (CI) diagnosed by abnormal troponin levels. The aim of the present study was to analyse the clinical characteristics of a large series of hospitalized patients for COVID‐19 in order to identify predisposing and/or protective factors of CI and the outcome. Methods and results: This is an observational, retrospective study on patients hospitalized in two Italian centres (San Raffaele Hospital and Cremona Hospital) for COVID‐19 and at least one high‐sensitivity cardiac troponin (hs‐cTnt) measurement during hospitalization. CI was defined if at least one hs‐cTnt value was above the 99th percentile. The primary end‐point was the occurrence of CI during hospitalization. We included 750 patients (median age 67, IQR 56–77 years; 69% males), of whom 46.9% had history of hypertension, 14.7% of chronic coronary disease and 22.3% of chronic kidney disease (CKD). Abnormal troponin levels (median troponin 74, IQR 34–147 ng/l) were detected in 390 patients (52%) during the hospitalization. At multivariable analysis age, CKD, cancer, C‐reactive protein (CRP) levels were independently associated with CI. Independent predictors of very high troponin levels were chronic kidney disease and CRP levels. Patients with CI showed higher rate of all‐cause mortality (40.0% vs. 9.1%, p = 0.001) compared to those without CI. Conclusion: This large, multicentre Italian study confirmed the high prevalence of CI and its prognostic role in hospitalized patients with COVID‐19, highlighting the leading role of systemic inflammation for the occurrence of CI.